Ecological Values in Tradition Kajang Community Weaving: Implications for Preservation Culture and Environment - Feby Triadi; Muhammad Asdar; Nur Faidzaturrahmah; Sarmianti Ansar; M. Awaluddin (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
Study This aim for study mark ecological in tradition weaving the Kajang community and the implications to preservation culture and environment. Focus study directed at tradition Tope Le'leng or sarong black as material culture that is not only functioning as product textiles traditional, but also as symbol identity, simplicity, compliance customs and relations harmonious man with nature. Research This use approach qualitative with method ethnography ecological. Data collected through observation participatory, interview in-depth, documentation, and search source relevant written research results. show that mark ecological in tradition Kajang weaving seen in use material natural, especially leaf tarum as dyes, utilization tool weaving traditional made from wood and bamboo, as well as the ongoing production process slow and limited. Tope Le'leng also have meaning symbolic in life social, customs and rituals of the Kajang people, especially as marker simplicity, equality and obedience to Pasang ri Kajang. In addition, the tradition weaving play a role in preservation culture through inheritance knowledge local, especially by women weavers, at the same time show a sustainability model-based wisdom custom. Research This confirm that Tope Le'leng is knot important between material culture, ethics ecology, spirituality and identity Kajang community. Preservation tradition Kajang weaving with thus need placed as part from effort guard culture at a time nurse environment.